The influence of idealised and non-idealised models on the effectiveness of advertisements and body appreciation in females - Wallhead, Georgia; Furnham, Adrian; McClelland, Alastair (Frontiers in Communication, 2025)
As social media advertising becomes increasingly influential, understanding the impact of different model representations on both consumer attitudes and body image is crucial. This study extends the existing literature by investigating the effects of using different sized models in social media advertising, examining the impact of the advertisements on body appreciation, and using memory and brand attitude as measures of advertisement effectiveness. In all, 235 young female participants from the United Kingdom viewed advertisements containing either “idealised” (thin) models or “non-idealised” (plus-size) models embedded within a simulated Instagram feed. Body Appreciation Scale (BAS) scores were taken pre-exposure and post-exposure to the advertisements. Advertisement effectiveness was measured via brand attitude and memorability of advertising information (free recall and recognition). Participants exposed to non-idealised models demonstrated a significant increase in BAS scores, whereas there was no effect for idealised models. There was a significant main effect of model type on brand attitude and free recall: non-idealised models elicited more positive brand attitudes and higher recall of brands/products compared to idealised models, but no significant effects were found for brand recognition. For participants exposed to idealised models, there was a significant positive relationship between their pre-exposure BAS scores and brand attitude scores, potentially explained by the perceived similarity between the participant and the model. The implications of using non-idealised models in advertisements for advertisers and consumers are discussed, and suggestions for future research are outlined.